Phenomena Doppelmayr's celestial atlas - Sparrow, Giles 1970- (The University of Chicago Paress, 2022)
"Lavishly illustrated volume revealing the intricacies of a 1742 map of the cosmos. The expansive and intricate Atlas Coelestis, created by Johann Doppelmayr in 1742, set out to record everything known about astronomy at the time, covering constellations, planets, moons, comets, and more, all rendered in exquisite detail. Through stunning illustrations, historical notes, and scientific explanations, Phenomena contextualizes Doppelmayr's atlas and creates a spectacular handbook to the heavens. Phenomena begins by introducing Doppelmayr's life and work, placing his extraordinary cosmic atlas in the context of discoveries made in the Renaissance and Enlightenment and highlighting the significance of its publication. This oversized book presents thirty beautifully illustrated and richly annotated plates, covering all the fundamentals of astronomy--from the dimensions of the solar system to the phases of the moon and the courses of comets. Each plate is accompanied by expert analysis from astronomer Giles Sparrow, who deftly presents Doppelmayr's references and cosmological work to a modern audience. Each plate is carefully deconstructed, isolating key stars, planets, orbits, and moons for in-depth exploration. A conclusion reflects on the development of astronomy since the publication of the Atlas and traces the course of the science up to the present day. Following the conclusion is a timeline of key discoveries from ancient times onward along with short biographies of the key players in this history"--Publisher's website
Includes glossary
Keywords: Doppelmayr, Johann Gabriel -- 1677-1750 -- Atlas coelestis; Stars / Atlases / Early works to 1800; Stars / Atlases / History; Astronomy / Charts, diagrams, etc / Early works to 1800; Science / History; Astronomy; Science; Stars; Charts, diagrams, etc; Early works; History; Scientific atlases